Gender violence in peace and war: states of complicity - Sanford, Victoria; Stefatos, Katerina; Salvi, Cecilia M. (Genocide, political violence, human rights series, 2016)
"A much-needed analysis of the role of the state, its mechanisms and structures in perpetuating, legitimizing and facilitating gender violence worldwide in the first decade and a half of the 21st century. This book documents the nature, extent and progress made in relation to gender-based violence since the advancements in women's rights that had their zenith in the 1990s, and focuses specifically on state participation in and interventions on gender violence. Gender Violence in Peace and War concentrates on gender violence in relation to state practices because, as the chapters clearly demonstrate, sexual victimization, torture, persecution, socioeconomic exclusion and domestic violence fall within the purview of the state and its proxies. Additionally, while gender, violence and the state are frequent and well-analyzed objects of study in social scientific and feminist literature, the full extent of this multilayered relation between all three has not been fully explored in recent social science literature and feminist scholarship in an interdisciplinary context"--Provided by publisher